2011
DOI: 10.4132/koreanjpathol.2011.45.s1.s20
|View full text |Cite
|
Sign up to set email alerts
|

Primary Myoepithelioma of the Testis - A Case Report -

Abstract: Myoepitheliomas are well-established to occur in the salivary glands, but they have also been described in the breast, upper aerodigestive tract, skin, and soft tissues. We report here on a unique case of primary myoepithelioma that occurred in the right testis of a 28-year-old man. The tumor was entirely confined to the testis and it was clearly separated from the epididymis. Histopathology revealed mixed architectural patterns in which the reticular areas merged into the chondromyxoid stroma. The tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The tumor presents as a painless or painful mass in the dermis, subcutis, or deep soft tissue 3,4. While most myoepitheliomas are of salivary gland origin, they have been reported in the soft tissue, retroperitoneum,3 lung,5 and testis 6. The histogenesis of myoepithelial tumors arising in soft tissue is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor presents as a painless or painful mass in the dermis, subcutis, or deep soft tissue 3,4. While most myoepitheliomas are of salivary gland origin, they have been reported in the soft tissue, retroperitoneum,3 lung,5 and testis 6. The histogenesis of myoepithelial tumors arising in soft tissue is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Myoepitheliomas proliferate from specialized contractile myoepithelial cells, which are present in the salivary glands, breast, respiratory tract, and skin . Myoepithelial tumours have been reported in the breast , tracheobronchial structures , soft tissue , larynx , cranial dura , sinonasal cavity , palate , retroperitoneum , vulva , testis , bone , and skin . These are often found in the salivary glands, although they only represent 1.5% of all salivary gland tumours .…”
mentioning
confidence: 99%
“…106,107,104 Other carbonaceous templates. Besides CNT and graphene, other carbonaceous templates like carbon coils, 108,109 carbon aerogel, 110 poly carbonate 111,112 and carbon cloth 113 were used for ALD coating. Qin et al demonstrated a route to synthesize plasmonic nanopeapods by ALD of Al 2 O 3 using helical carbon nanocoils.…”
Section: Ecs Transactions 75 (6) 47-68 (2016)mentioning
confidence: 99%